MAYA ANGELOU’S PROTEST CULTURE FOR THE OPPRESSED - Athiphro, Ashihrii; Singh, H Subrata (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper analyses Maya Angelou’s crucial role in creating a culture of protest for the oppressed, with a focus on feminism, resilience, and the battle against systematic injustices. Angelou’s writings, which include her poetry and autobiographies, represent the sufferings of Black women and the marginalized people emphasizing how cultural identity can serve as both a source of strength and a means of survival for marginalized communities serving as both a testament and a rallying cry against oppression. Her work often underscores the importance of cultural pride and the resilience of oppressed people. Angelou’s literature promotes an intersectional approach to feminism, emphasizing adaptability in the face of hardship, using themes of self-worth, strength, resistance and remembering one’s heritage as a means of overcoming adversity. Her message is one of both personal and cultural empowerment, suggesting that holding onto one’s culture is not only an act of survival but also an act of resistance against forces of oppressions. Maya Angelou’s themes of identity, feminism, resilience, and empathy would resonate deeply in today’s social media culture. Through her feminist messages, she would challenge gender norms and beauty standards, inspiring women to embrace inner strength. Her emphasis on empathy would remind people of the lasting impact of kindness, promoting respectful, compassionate interactions in the digital world. In today’s digital age, her remarks reverberate across social media platforms, creating solidarity and motivating future generations of activists. This paper will discuss on how Angelou’s legacy continues to influence modern movements through her works on her offline books and even through social media platforms, establishing her work as a key voice in ongoing struggles for social justice and gender equality and her influence on NE Indian women.